2021
DOI: 10.1177/02711214211007572
|View full text |Cite
|
Sign up to set email alerts
|

Using Peer Coaches as Community-Based Competency Drivers in Part C Early Intervention

Abstract: Using an implementation science framework, this study examines the impact of a multicomponent professional development (PD) approach implemented by internal peer coaches on early intervention providers’ use of Family Guided Routines-Based Intervention. The experimental study used a single-case multiple baseline design across participants, replicated in three sites with early interventionist (EI) providers ( n = 9) and families with infants and toddlers ( n = 18) in community-based Part C programs. Data indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This discrepancy between recommendations and practice may be in part due to insufficient provider pre- and in-service training in working directly with caregivers (see Romano & Schnurr, 2022). Recent professional development approaches (e.g., Embedded Practices and Intervention with Caregivers, Salisbury et al, 2018; Family Guided Routines-Based Intervention, Kashinath, Woods, & Goldstein, 2006) have indicated some promise in increasing the proportion of time that providers work directly with caregivers, though most studies examining these approaches are small (Krick Oborn & Johnson, 2015; Romano et al, 2021; Salisbury et al, 2018). More research is needed to further develop and establish efficacy of these professional development frameworks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy between recommendations and practice may be in part due to insufficient provider pre- and in-service training in working directly with caregivers (see Romano & Schnurr, 2022). Recent professional development approaches (e.g., Embedded Practices and Intervention with Caregivers, Salisbury et al, 2018; Family Guided Routines-Based Intervention, Kashinath, Woods, & Goldstein, 2006) have indicated some promise in increasing the proportion of time that providers work directly with caregivers, though most studies examining these approaches are small (Krick Oborn & Johnson, 2015; Romano et al, 2021; Salisbury et al, 2018). More research is needed to further develop and establish efficacy of these professional development frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 89% of the time was spent addressing child-specific skill development, and less than 5% on family or other issues, including caregiver concerns and basic family needs, in contrast to recommendations for a whole family-centered approach. More recent work has continued to suggest that, outside of emerging specific professional development efforts focused entirely on caregiver coaching (e.g., Embedded Practices and Intervention with Caregivers, Salisbury et al, 2018), provider use of explicit teaching and direct coaching methods remains rare (Meadan et al, 2018;Romano, Schnurr, Barton, Woods, & Weigel, 2021;Sawyer & Campbell., 2017). Even in studies in which caregivers reported that they valued coaching strategies and used them frequently, strategies involving direct caregiver practicing, teaching, and giving feedback were the most rarely used, while having the caregiver observe the practitioner interacting with the child were the most used (Douglas et al, 2020;Meadan et al, 2018).…”
mentioning
confidence: 99%
“…This argument supports an earlier work by Cohen, Higgins, Sanyal and Harris (2008) who asserted that community coaching was an "innovative" approach to community development initiatives. Similarly, several scholars have alluded to the value of community coaching in the field of health, including community health coaching (Holland, Greenberg, Tidwell, Malone, Mullan, & Newcomer, 2005), the management of HIV self-testing services (Dunkley, Wang, Worrall, Skipper, & Evans, 2017), safe handling of agricultural pesticides (Ibrahim, Tawfik, & El Lassy, 2018), obesity management (Heerman, Cole, Teeters, Lane, Burgess, Escarfuller, Bonnet, Barkin, & Schlundt, 2019), and disabilities (Romano, Schnurr, Barton, Woods, & Weigel, 2021).…”
Section: Understanding Community Coaching and Community Mentorshipmentioning
confidence: 99%